Digitalisasi UMKM Sebagai Strategi Naik Kelas: Studi Kasus Rumah Tahu dan Tempe Bu Ratni: Penelitian - Milcha Handayani Tammubua; Victor Pattiasina; Nur Fadillah indah P; Wa Ode Maharani; Resa Iriani; Mathilda Adolfina Gebze; Rahel Ta’dung; Bunga Dahlia; Muji Lestari; Nurul Ana Mutmainnah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the impact of digitalization on the management of the Bu Ratni Tofu and Tempe House MSME. The program was implemented through several stages, including observation, needs analysis, training, mentoring, and evaluation. The results showed that before the program was implemented, the Bu Ratni Tofu and Tempe House MSME did not have structured financial records, did not use digital payment methods, and did not utilize technology-based promotional media. Through training and mentoring, there was a significant increase in the implementation of simple bookkeeping, the adoption of QRIS as a means of digital payment transactions, and the use of social media as a promotional tool. Digitalization has been proven to improve financial literacy, simplify transactions, expand promotional reach, and drive increased sales. Thus, the digitalization program has proven effective in encouraging MSMEs to grow and move up a class in the modern business era.